Phylogenetic relationships of Triplaris and Ruprechtia: Re-delimitation of the recognized genera and two new genera for tribe Triplarideae (Polygonaceae) (2011)
Recent phylogenetic work has increased our knowledge of the relationships within Polygonaceae. However, few studies have explored the generic relationships within Eriogonoideae. Two understudied genera are Triplaris and Ruprechtia (tribe Triplarideae), a group of approximately 55 Neotropical species of trees, shrubs, and lianas. The generic classification of Triplaris and Ruprechtia has been unstable mostly due to different taxonomic interpretations and the difficulty of characterizing each genus morphologically. Although some studies have proposed diagnostic morphological characters for each, most have exceptions. In this study, we explored the phylogenetic relationships of 32 species of Triplaris and Ruprechtia using four chloroplast (matK, ndhF, rps16-trnK, ndhC-trnV), and two nuclear regions (ITS, second intron of Leafy). Results confirm the monophyly of Triplaris, but Ruprechtia is polyphyletic. To maintain monophyletic genera, two new names are proposed: Magoniella and Salta . The two new genera are formally described and morphological synapomorphies are proposed for the four genera of Triplaridae. Three species are transferred to these new genera, Salta triflora , Magoniella laurifolia , and M. obidensis.